Perceptions on clinical learning environment among Diploma Nursing students in Kubang Kerian Nursing College, Kelantan and School Of Health Sciences, Universiti Sains Malaysia - Mui, Lim Siew (Universiti Sains Malaysia, 2013)
The clinical learning environment (CLE) is a complex social entity that influences students’ learning in the clinical setting during clinical placement. Failure to provide relevant clinical experiences has ramifications not only on students but also for the nursing program and the profession. For nursing students, a poor clinical experience can lead to disillusionment about nursing and failure to integrate and learn during clinical placement. A cross-sectional study was conducted to investigate how diploma nursing students’ perceptions of their clinical learning environments after obtaining ethical approval from the USM ethics committees, the Dean of School of Health Sciences, USM and Director of Kubang Kerian Nursing College (KKNC), Kelantan. The nd and 3rd participants were 2' year diploma nursing students enrolled in the Nursing Programme in Kubang Kerian Nursing College (KKNC), Kelantan and School of Health Sciences, Universiti Sains Malaysia (USM). Simple random sampling was used to select the sample. Participants were invited to complete the questionnaire: Clinical Learning Environment, Supervision and Nurse Teacher (CLES+T). Data were analyzed using the SPSS version 20. Of the 420 participants from both KKNC and USM, a total of 200 diploma nursing students (2nd and 3rd Year) participated in this study (n=200). Hundred diploma nursing students were from the KKNC (n=100) and hundred from USM (n—100). The study revealed that the participants were generally satisfied with their clinical placements. There was a good correlation between the three sub dimensions of CLES+T: correlation between the learning environment and the 0.548) and the correlation between the supervisory relationship and the role of nurse teacher (p<0.001, r= 0.578) that affect diploma nursing students' perceptions regarding their clinical learning environment. For the occurrence of supervision, the study indicated that overall there were nearly half (45.0%) of the students experienced group supervision relationship. The majority of the students (30.5%) had once or twice separate private unscheduled supervision during a week. This study found that there was a significant mean score difference between ethnicity and the diploma nursing students (KK.NC and USM) perceptions regarding their clinical learning environment (p=0.025). Malay nursing students were having better perceptions regarding CLE. The study highlights a need to provide a supportive and healthy clinical learning environment. A through understanding of nursing students' perceptions of their CLE by nursing authorities is important in improving the quality of CLE.